Supervision on Transference and Counter-Transference Issues for Undergraduate Studentsâ Counseling Practice at Counseling Department - Diniaty, Amirah (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
Undergraduate students should take 4 credits for counseling practice subject in Counseling Department of State Islamic University of Riau. The subject is taken by seventh semester students who conduct counseling practice at senior high school for 3 months. Based on prelimenary study, majority of students acknowledged that they felt nervous to follow this programme. Thus, the problem of transference and counter transference issue for undergraduate students counseling practice must be answered by their supervisions. The result showed that a total of 93% of respondents had positive transference, while 7% of them had negative one. It means that majority of respondents felt positive transference, while internship students faced identification counter transference. It was proved that internship students did not need to have negative thinking of being rejected by the schools. The finding also showed that 97.3% of interenship students faced identification counter transference, while 2,7%Â of them experienced for unidentification of transfenece. It means that there were a few of them should be supervised to have good counter transference. Supervision format that done by supervisor (university teacher) and tutor (high school teacher) was by conducting monthly meeting and by following up counseling result and writing report. It is recommended that a professional discussion is conducted to discuss problems faced by internship students.